Reptin/RUVBL2 is required for hepatocyte proliferation in vivo, liver regeneration and homeostasis. (19th April 2021) - Javary, Joaquim; Allain, Nathalie; Ezzoukhry, Zakaria; Di Tommaso, Sylvaine; Dupuy, Jean‐William; Costet, Pierre; Dugot‐Senant, Nathalie; Saltel, Frédéric; Moreau, Violaine; Dubus, Pierre; Benhamouche‐Trouillet, Samira
Abstract: Previous studies have shown that Reptin is overexpressed in hepatocellular carcinoma and that it is necessary for in vitro proliferation and cell survival. However, its pathophysiological role in vivo remains unknown. We aimed to study the role of Reptin in hepatocyte proliferation after regeneration using a liver Reptin knock‐out model ( Reptin LKO ). Interestingly, hepatocyte proliferation is strongly impaired in Reptin LKO mice 36 h after partial hepatectomy, associated with a decrease of cyclin‐A expression and mTORC1 and MAPK signalling, leading to an impaired liver regeneration. Moreover, in the Reptin LKO model, we have observed a progressive loss of Reptin invalidation associated with an atypical liver regeneration. Hypertrophic and proliferative hepatocytes gradually replace Reptin KO hypotrophic hepatocytes. To conclude, our results show that Reptin is required for hepatocyte proliferation in vivo and liver regeneration and that it plays a crucial role in hepatocyte survival and liver homeostasis.